Analysis of Millennial Consumption Behavior Factors and Their Interest in Visiting Sundanese Restaurants in Bandung - Nikmah, Nur Faijatun; Sudono, Agus; Fajri, Ilham (Gastronomy Tourism Journal, 2019)
The growth of people who are growing rapidly is the background of this study and the aim is to get an idea of the millennial potential in Bandung and analyze what factors most dominate millennial food consumption behavior towards interest led to Sundanese restaurants in Bandung. This study uses quantitative descriptive methods with data collection techniques in the form of question items on the questionnaire. The Sundanese restaurant and the experience of the visit itself became a place to do this research. Participants involved in this study were 270 respondents. Analysis was performed on the data obtained that is in the beginning of the researxh, while doing the research, and in the end of the research. The data analysis technique used is Exploratory Factor Analysis. The results of the analysis obtained showed that Bandung population of 27.99 percent is in the range of the age group of 20-34 years with a total of 699,395 thousand inhabitants dominated by vulnerable people aged 20-24 years which is around 10, 36 percent of the profession as students / students and income less than Rp 2,500,000 per month. Then, it was found that only nine factors that is influencing millennial consumption behavior towards their interest in visiting Sundanese restaurants in Bandung. They are: food characteristic, positive feeling, influence from external world, environmental in an attractive destination, food experience, negative feelings, relationships, looking for unique and authentic experiences, and fulfillment of physical and psychological needs. From the nine factors mentioned, the most dominating factor is the food characteristic factor with an eigenvalue value of 8,790.